2017
DOI: 10.1089/sur.2017.144
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Approach to Surgical Exposure Reduces Surgical Site Complications after Bilateral Lung Transplantation

Abstract: Tailoring the operative approach can reduce surgical site complications in lung transplant patients by avoiding a clamshell whenever feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, there are clearly several scenarios in which CPB may be necessary, and there are many proponents of CPB who have been able to achieve good results with it after LTx. 1,2,8,[19][20][21] But the current data suggest a heightened risk of postoperative graft dysfunction with CPB that should be weighed against the potential gains in each individual scenario.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, there are clearly several scenarios in which CPB may be necessary, and there are many proponents of CPB who have been able to achieve good results with it after LTx. 1,2,8,[19][20][21] But the current data suggest a heightened risk of postoperative graft dysfunction with CPB that should be weighed against the potential gains in each individual scenario.…”
Section: Discussionmentioning
confidence: 89%
“…4,6,7 Yet other studies have shown excellent outcomes with CPB, including favorable graft function and survival, even with higher-risk recipients and donors. 1,[8][9][10][11] ECMO has become a popular mode of intraoperative support because it can provide gas exchange and hemodynamic stability while reducing the amount of extracorporeal tubing and volume reservoir, which increase the risk of inflammation. 6,12 A study by Hoetzenecker and colleagues 3 showed remarkably low rates of PGD in LTx performed with routine use of venoarterial ECMO.…”
Section: Central Messagementioning
confidence: 99%
“…As a systemic metabolic disease, obesity has become a serious global problem threatening human health (23). BMI >24 kg/m 2 will produce different degrees of symptoms of respiratory tract stenosis due to the increase of fat in the inner wall of the respiratory tract, and as a large operation, lung transplantation will cause a stress response in the body, aggravate a local inflammatory response, and increase the probability of incision infection (24). At the same time, because obese patients have more subcutaneous fat accumulation, and the sutures of lung transplantation are relatively tight, this will further increase the accumulation of subcutaneous fat at the surgical site, increasing the probability of fat liquefaction (25).…”
Section: Body Mass Index (Bmi) Of the Organ Recipientmentioning
confidence: 99%
“…Median sternotomy is another approach for BS-LTx. This approach has been shown to have a lower risk of chest wall complications compared to the clamshell approach, likely due to preservation of the internal mammary arteries and improved early chest wall mechanics (10,11). This approach can be considered in patients with minimal pleural adhesions and appropriate hilar depth.…”
Section: Sternotomymentioning
confidence: 99%
“…The feasibility can be predicted from preoperative CT imaging measuring the hilar depth and degree of pleural thickening (10). Elde et al (10) reserved the median sternotomy approach for patients with left main bronchus depth less than 12 cm and a midline to cardiac apex distance of less than 10 cm. The major downside for using a median sternotomy is that intra-operative MCS (CPB or VA ECMO) is typically needed for hemodynamic support while manipulating the heart for exposure of the hilar dissection and anastomosis.…”
Section: Sternotomymentioning
confidence: 99%